Photovoltaic Counter Electrodes: An Alternative Approach to Extend Light Absorption Spectra and Enhance Performance of Dye‐Sensitized Solar Cells. Issue 3 (14th February 2019) - Ma, Dui; Zai, Jiantao; Wang, Yan; Qiao, Qiquan; Qian, Xuefeng
Abstract: If counter electrodes (CEs) could also contribute to light harvesting in dye‐sensitized solar cells (DSSCs), then the power conversion efficiency (PCE) of DSSCs would be further boosted without changing the device structure. Nearly monodispersed Ag2 Se nanocrystals with a bandgap of 1.62 eV (∼765 nm) were synthesized via a one‐pot process, and Ag2 Se CEs were fabricated by using a spin‐coating and annealing process. Incident photon‐to‐current conversion efficiency and photocurrent spectra indicated that Ag2 Se CEs can generate the electricity by harvesting more visible light, which could not be absorbed by dye‐sensitized photoanodes. Thus, compared to Pt CE (7.57 %), the DSSC based on Ag2 Se CE exerted a higher PCE of 8.06 %. The development of photovoltaic CEs may offer an alternative way to promote the performance and competitiveness of DSSCs. Abstract : Photovoltaic counter electrodes not only catalyse I3 − reduction, but also harvest transmitted photons of photoanodes to increase the photocurrent of DSSCs (see figure). This offers an alternative method for enhancing the performance and competitiveness of DSSCs.